Pericytes Favor Oligodendrocyte Fate Choice in Adult Neural Stem Cells - Silva, Maria Elena; Lange, Simona; Hinrichsen, Bryan; Philp, Amber R.; Reyes, Carolina R.; Halabi, Diego; Mansilla, Josselyne B.; Rotheneichner, Peter; Guzman de la Fuente, Alerie; Couillard-Despres, Sebastien; Bátiz, Luis F.; Franklin, Robin J. M.; et al. (Frontiers in Cellular Neuroscience, 2019)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Upon demyelination, oligodendrocyte progenitor cells (OPCs) are activated and they proliferate, migrate and differentiate into myelin-producing oligodendrocytes. Besides OPCs, neural stem cells (NSCs) may respond to demyelination and generate oligodendrocytes. We have recently shown that CNS-resident pericytes (PCs) respond to demyelination, proliferate and secrete Laminin alpha2 (Lama2) that, in turn, enhances OPC differentiation. Here, we aimed to evaluate whether PCs influence the fate choice of NSCs in vitro, towards the production of new myelin-producing cells. Indeed, upon exposure to conditioned medium derived from PCs (PC-CM), the majority of NSCs gave rise to GalC- and MBP-expressing oligodendrocytes at the expense of the generation of GFAP-positive astrocytes. Consistent with these findings, PC-CM induces an increase in the expression of the oligodendrocyte fate determinant Olig2, while the expression level of the astrocyte determinant ID2 is decreased. Finally, pre-incubation of PC-CM with an anti-Lama2 antibody prevented the generation of oligodendrocytes. Our findings indicate that PCs-derived Lama2 instructs NSCs to an oligodendrocyte fate choice favouring the generation of myelin-producing cells at the expense of astrocytes in vitro. Further studies aiming to reveal the role of PCs during remyelination may pave the way for the development of new therapies for the treatment of MS.